GEM‐CEDAR challenge: Poynting flux at DMSP and modeled Joule heat. Issue 2 (18th February 2016) - Rastätter, Lutz; Shim, Ja Soon; Kuznetsova, Maria M.; Kilcommons, Liam M.; Knipp, Delores J.; Codrescu, Mihail; Fuller‐Rowell, Tim; Emery, Barbara; Weimer, Daniel R.; Cosgrove, Russell; Wiltberger, Michael; Raeder, Joachim; et al.
Abstract: Poynting flux into the ionosphere measures the electromagnetic energy coming from the magnetosphere. This energy flux can vary greatly between quiet times and geomagnetic active times. As part of the Geospace Environment Modeling‐coupling energetics and dynamics of atmospheric regions modeling challenge, physics‐based models of the 3‐D ionosphere and ionospheric electrodynamics solvers of magnetosphere models that specify Joule heat and empirical models specifying Poynting flux were run for six geomagnetic storm events of varying intensity. We compared model results with Poynting flux values along the DMSP‐15 satellite track computed from ion drift meter and magnetic field observations. Although being a different quantity, Joule heat can in practice be correlated to incoming Poynting flux because the energy is dissipated primarily in high latitudes where Poynting flux is being deposited. Within the physics‐based model group, we find mixed results with some models overestimating Joule heat and some models agreeing better with observed Poynting flux rates as integrated over auroral passes. In contrast, empirical models tend to underestimate integrated Poynting flux values. Modeled Joule heat or Poynting flux patterns often resemble the observed Poynting flux patterns on a large scale, but amplitudes can differ by a factor of 2 or larger due to the highly localized nature of observed Poynting flux deposition that is not captured by the models. In addition, the positioning of modeled patterns appear to be randomly shifted against the observed Poynting flux energy input. This study is the first to compare Poynting flux and Joule heat in a large variety of models of the ionosphere. Key Points: Poynting flux from DMSP were compared with modeled Joule heat in GEM‐CEDAR challenge Physics‐based and empirical models were evaluated for the first time Empirical model shows weaker maximum Poynting flux than observatioin and most physics‐based models